Carbon Quantum Dots Promote Coupled Valence Engineering of V2O5 Nanobelts for High‐Performance Aqueous Zinc‐Ion Batteries. Issue 9 (18th March 2021) - Zhang, Jingrui; Wei, Shuxian; Wang, Haowei; Liu, Huanhuan; Zhang, Yi; Liu, Siyuan; Wang, Zhaojie; Lu, Xiaoqing
Abstract: Aqueous Zn‐ion batteries (ZIBs) have acquired the researchers' curiosity owing to their harmlessness, cost effectiveness and high theoretical capacity of Zn anode. However, desirable cathode materials with high‐capacity and high‐rate are still scarce. In this work, the formation of carbon quantum dots induced vanadium pentoxide nanobelts was demonstrated via a facile one‐step hydrothermal method for ZIBs. It exhibited an excellent Zn ion storage capacity of 460 mA h g −1 at 0.1 A g −1, superior rate capability and stable cycling performance (above 85 % capacity retention over 1500 cycles at 4 A g −1 ). The electrochemical kinetics and zinc ion storage mechanism were also considered. An efficient architecture‐coupled valence engineering in the hybrid cathode was proposed to improve the electric conductivity, Zn ion diffusion rate, and cycling stability for ZIBs. This work may be a great motivation for further research on V2 O5 or other vanadium‐based materials for high‐performance ZIBs. Abstract : Zinc ion batteries : Simple simultaneous reduction and morphological control by glucose during hydrothermal reaction construct carbon quantum dots decorated V 4+ ‐rich V2 O5 nanobelts, endowing the zinc ion battery with high capacity, good rate performance, and stability.